2004
DOI: 10.1081/pfc-200026903
|View full text |Cite
|
Sign up to set email alerts
|

MSMA Resistance Studies

Abstract: Monosodium methanearsonate (MSMA)-resistant and -susceptible common cocklebur (Xanthium strumarium L.) and cotton (Gossypium hirsutum L.) were treated with MSMA. Plant parameters analyzed were: glutathione synthetase activity, selected amino acid (arginine, glutamic acid, alanine, citrulline, glutamine, and glutathione) content and arsenic content (MSMA, total arsenic, and arsonate). No reduction of arsenic from the parent pentavalent form present in MSMA to the trivalent form was detected. Arginine, glutamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, Keese and Camper (2006) later refuted this conclusion, as minimal change in cuticle concentrations was observed. Camper et al (2004) then suggested that cotton tolerance to MSMA could be related to glutathione synthetase activity and possibly to the presence of phytochelatins. However, Pima cotton leaves usually contain more waxy cuticles on the surface, which could reduce absorption of MSMA in leaves and therefore prevent crop injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, Keese and Camper (2006) later refuted this conclusion, as minimal change in cuticle concentrations was observed. Camper et al (2004) then suggested that cotton tolerance to MSMA could be related to glutathione synthetase activity and possibly to the presence of phytochelatins. However, Pima cotton leaves usually contain more waxy cuticles on the surface, which could reduce absorption of MSMA in leaves and therefore prevent crop injury.…”
Section: Discussionmentioning
confidence: 99%